2016
DOI: 10.1177/1065912916663653
|View full text |Cite
|
Sign up to set email alerts
|

Representation on the Courts? The Effects of Trial Judges’ Sex and Race

Abstract: Scholars have long sought to resolve whether and to what degree political actor diversity influences the outputs of political institutions like legislatures, administrative agencies, and courts. When it comes to the judiciary, diverse judges may greatly affect outcomes. Despite this potential, no consensus exists for whether judicial diversity affects behavior in trial courts—that is, the stage where the vast majority of litigants interact with the judicial branch. After addressing the research design limitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 63 publications
1
54
0
Order By: Relevance
“…In the study by Cox & Miles (2008) that we discussed above, the authors found that the effect of race on the outcome of Section 2 claims under the VRA was much stronger than the effect of politics alone. Similarly, African-American federal district judges more often rule favorably for plaintiffs on pretrial motions in race or gender discrimination cases than white judges (Boyd 2016). Another study also showed that white federal judges are less sympathetic to employment discrimination claims than minority judges---especially in pro se cases (Weinberg & Nielsen 2011).…”
Section: Racementioning
confidence: 97%
“…In the study by Cox & Miles (2008) that we discussed above, the authors found that the effect of race on the outcome of Section 2 claims under the VRA was much stronger than the effect of politics alone. Similarly, African-American federal district judges more often rule favorably for plaintiffs on pretrial motions in race or gender discrimination cases than white judges (Boyd 2016). Another study also showed that white federal judges are less sympathetic to employment discrimination claims than minority judges---especially in pro se cases (Weinberg & Nielsen 2011).…”
Section: Racementioning
confidence: 97%
“…These are helpfully summarized by Boyd (2016) in the context of the gender of trial judges (see also Haire and Moyer, 2015). A related concept-that of panel effects, which we discuss below-also posits that these judges might not only reach different conclusions, but also influence their colleagues' votes via panel effects (Boyd, Epstein and Martin, 2010;Kastellec, 2013).…”
Section: Why Might Judges Of Different Backgrounds Vote Differently?mentioning
confidence: 99%
“…Female judges, black judges, and other non-white, non-male judges "bring a unique knowledge base and expertise to the bench" (Boyd, 2016, p. 789). This knowledge is particularly salient in situations where it is most applicable-such as cases or issues that touch upon race, gender, or identity (Boyd, 2016;Boyd, Epstein and Martin, 2010;Kastellec, 2013). This theory is perhaps the closest to Sotomayor's comment that a "wise Latina" would reach a conclusion different than "a white male who hasn't lived that life" (though, of course, none of these theories imply that a "wise Latina" would reach a "better conclusion").…”
Section: Why Might Judges Of Different Backgrounds Vote Differently?mentioning
confidence: 99%
“…Scholars have extensively demonstrated that judges disagree with one another about how to decide similar cases (for recent examples, see Boyd 2016;Boyd, Epstein, and Martin 2010;Epstein, Landes, and Posner 2013;Kastellec 2013). Intermediate appellate courts are required to hear (properly filed) appeals from trial courts and therefore cannot avoid making these overly negative inferences.…”
Section: Fact Finding In the Judicial Hierarchymentioning
confidence: 99%